Literasi Kesehatan: PHBS sebagai Upaya perawatan Kesehatan Pasca Bencana pada Masyarakat Pesisir melalui Peer Edukasi - Harlina Rusiana; Lalu Amri Yasir; Rias Pratiwi Safitri; Baiq Nurul Hidayati; Anna Layla Salfarina (Insan Kreasi Media, 2026)
Disasters in coastal areas often lead to further health problems, particularly related to clean and healthy living behaviors (PHBS), environmental sanitation, and low community preparedness in dealing with post-disaster conditions. This community service activity aims to improve health literacy in coastal communities in Taman Ayu Gerung by involving the TSBD as a local driver. The community service method is carried out in a participatory manner through the stages of preparation, identification of health problems, implementation of health literacy, mentoring health practices, and evaluation. Literacy is provided through interactive lectures, discussions, questions and answers, visual presentations, and simulations of handwashing practices, clean water use, household waste management, and post-disaster first aid. The results of the community service show an increase in participants' understanding of PHBS and handling health problems after a disaster, as well as the formation of an active role of TSBD as peer educators who are able to continue education to other community groups. These findings emphasize the importance of a community-based approach to strengthening the health resilience of coastal communities in a sustainable manner.